THE MORAL COMPONENT AND ITS ROLE OF DEVELOPMENT AND FUNCTIONING OF THE ECONOMIC SYSTEM - Томашевская, Ольга; Зуйкова, Анна (SWorldJournal, 2021)
The preconditions for strengthening the role of morality in the economy and approaches to solving the dilemma «morality or (and) profit» are studied